Lower limb alignment in young female athletes is associated with knee joint moments during the drop vertical jump - Jacques Riad; Katarina Hjältman; Scott Coleman (Archives of Sports Medicine and Physiotherapy - Peertechz Publications, 2018)
Background: Increased rotational forces and knee valgus forces puts strain on the anterior cruciate ligament, frequently ruptured in female athletes. Increased internal hip rotation and increased knee valgus alignment, possible risk factors for anterior cruciate ligament rupture, are more common in women than men. Purpose: To study hip, knee and foot alignment related to forces in the knee joint during the drop vertical jump in young female athletes. Methods: Seventy-one female athletes, mean age 17.1 years (range 14.3-25.7 years) were recruited from regional handball and soccer teams. Participants underwent a physical examination on passive range of motion of the hip, knee and ankle at the Gait Analysis Laboratory. They also performed three drop vertical jumps from 31 cm height onto force plates. A three-dimensional motion analysis system was used.  Results and main findings: Physical examination revealed more internal hip rotation, mean 51.0 degrees (SD 8.5) than external rotation, mean 42.2 (SD 6.8), (p=0.001) and mean 1.1 degree valgus (SD 1.9).  Maximal external knee rotation moments were higher, mean 0.18 Nm/kg, than maximal internal rotation moment, mean 0.13 Nm/kg (p=0.001). The difference between the maximal valgus and varus moments was significant (p=0.001) although equal in size (0.21 Nm/kg), respectively. The degree of internal rotation of the hip on physical examination correlated positively with maximal external knee rotation moment, correlation coefficient=0.196 (p=0.019) in the drop vertical jump but correlated negatively with knee varus moment correlation coefficient = -0.175 (p=0.038). Thus, increased internal hip rotation is associated with higher external knee rotation moment and lower varus moment. Conclusion and summary: On physical examination, increased internal hip rotation, often present in females, is associated with increased forces in the knee joint during the drop vertical jump. Increased internal rotation of the hip could be a risk factor for anterior cruciate ligament rupture in young female athletes.  Clinical Relevance: The physical examination of alignment is easy to perform and could help identify individuals at risk of anterior cruciate ligament rupture. These athletes could be informed and possibly undergo special muscle and motor control training.